Curriculum change in modern foreign languages education in England: barriers and possibilities. Issue 5 (2nd September 2020) - Parrish, Abigail
ABSTRACT: This paper considers the languages on offer in secondary schools in England and the possibility of enacting curriculum change with a view to reducing the dominance of French, Spanish and, to a lesser extent, German as a possible way to increase take-up of modern foreign languages post-14. Questionnaires were completed by 666 students aged 14–15, 70 head teachers and 119 heads of modern languages in secondary schools throughout England, investigating students' views as to the languages they would like to learn and their views of particular languages as well as the views of senior and middle leaders on the factors which impact on the teaching of modern languages. The paper concludes that students are interested in a wider range of languages than is currently available, for reasons primarily relating to usefulness. It also finds that schools are constrained by operational concerns preventing them fully considering the possibility of teaching a wider range of languages. Implications for national-level language policy and the culture of school accountability are discussed.